Isolation of a chrystalline compound from Uvaria scandens, C.C. Rob. (Anonaceae) - Guevara, Beatrice Q.
A pentacyclic triterpene was isolated from Uvaria scandens by chromatographic methods. The triterpene (C30 H50 O) m.p. 282-283(degrees) was identified as taraxerol from its infrared and mass spectra and by comparative thin-layer chromatography and mixed-melting point determination with an authentic sample. Its acetyl ester derivative was prepared and a comparison was made of their infrared spectra and thin-layer chromatographic pattern.